Numerical and experimental evaluation of shear strength and consolidation properties of cohesive soils in high water table areas - Izhar, Nauman; Khan, Muhammad Adeel; Khan, Muhammad Salman; Khan, Asad; Ahmad, Mahmood; Sabri Sabri, Mohanad Muayad; Necurzac, Muriuzs; Alzlfawi, Abdullah (Frontiers in Earth Science, 2025)
The geotechnical properties of soil are crucial in determining the stability of foundations and construction safety in regions with high groundwater levels, such as Warsak Road in Peshawar, Pakistan. Due to its proximity to the Warsak Dam and intersecting irrigation canals, the area experiences a consistently high water table, which significantly impacts soil stability, leading to potential issues such as excessive settlement, reduced shear strength, and increased structural instability. These groundwater conditions pose unique challenges for foundation stability, making it essential to develop a comprehensive understanding of the soil’s consolidation behavior and shear strength properties. To address these concerns, this study employs a combined experimental and numerical approach, aiming to evaluate these critical soil properties in detail. The experimental phase involved collecting three undisturbed soil samples from each of the five distinct sites along Warsak Road, spaced approximately 5 km apart. These samples were subjected to standardized laboratory tests, including grain size distribution, specific gravity, Atterberg Limits, direct shear, unconfined compression, and oedometer tests, per ASTM standards. To further validate the laboratory findings, numerical analysis using PLAXIS software was conducted, along with analytical evaluations using the Meyerhof and Vesic bearing capacity equations. This integrated methodology provided a comprehensive understanding of the soil’s behavior under varying conditions, revealing distinct variations in the average values of the three samples from each site. Specifically, Site 1 exhibited an average cohesion of 18.22 kN/m2, making it suitable for low-rise structures, whereas Site 2, with an average cohesion of 15.23 kN/m2, indicated the need for stabilization due to its high consolidation potential. Site 3, averaging 13.3 kN/m2, showed higher settlement risk, necessitating deep foundations, while Site 4, with the lowest average cohesion of 9.94 kN/m2, was deemed unsuitable for heavy loads without reinforcement. In contrast, Site 5, having the highest average cohesion of 20.2 kN/m2, demonstrated excellent stability, ideal for multi-story buildings and other heavy structures. The numerical results from PLAXIS offered a more accurate understanding of soil behavior compared to the traditional Meyerhof and Vesic methods, highlighting the necessity of integrating advanced numerical techniques with conventional approaches. Accordingly, targeted soil improvement measures are recommended for weak and highly compressible soils to ensure the long-term stability and safety of structures in the region.